A critical inquiry into public funding and intervention in socially engaged art in Singapore - Li, Wanyu (Nanyang Technological University, 2022)
The role of art in society is an ever evolving one. Taking the popularity of programming, process-driven and collaborative modes of artmaking in Socially Engaged Art (SEA) projects as a point of departure, this paper highlights some key historical developments of art intervening in Singapore society and analyses the artistic value of participatory projects using the critical discourse of Claire Bishop’s text Artificial Hells. Through two case studies, the paper examines how the repositioning of artistic value expands the social context of art in Singapore, and the contemporary condition of SEA projects in Singapore.